EVALUASI PENERAPAN METODE JOB ORDER COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI (Studi Kasus pada PT. Organ Jaya) - Jeffry . (Jurnal Ilmiah Binaniaga, 2011)
PT . Jaya organ producing products based on orders received from customers , and therefore in determining the cost of production of PT . Jaya organs using job order costing. Production cost consists of raw material costs , direct labor costs and factory overhead costs. For the calculation of the cost of raw materials PT . Organ jaya calculate based on the existing formula , but for the cost of direct labor and factory overhead costs PT . Jaya organs not calculate accurately match the job order costing method . Both the cost is calculated based on the rates , so the cost of direct labor and factory overhead costs are absorbed by the product orders can not be calculated specifically. With job order costing method , PT . Organ Jaya will easily find the cost of production for each order , because in the calculation of the cost of production is not affected by the initial inventory of final goods as well as ordered , then the cost of production is the basis for determining the cost of production . Calculation of cost of production is carried out by PT . Jaya organ still manually so that the resulting lack of accurate information , in this case PT . Jaya organs not use time sheet and job cost ticket as a medium in the calculation of production costs in order to determine the cost of production . Keyword : Job order costing-overhead cost